Reactivity of quartzite aggregate to cement alkalis studied by means of standardised and NDT - Servando Chinchón-Payá; Luana Abreu; Julio Emilio Torres; Nuria Rebolledo; Javier Sánchez; Sylvia de Gregorio; Manuel Ordóñez (Case Studies in Construction Materials)
This study experimentally evaluates the alkali reactivity potential of a quartzite aggregate employed in the production of concrete for a low-emission radioactive waste storage facility. For comparison, a granitic aggregate and the Spratt's aggregate were also analysed. The study was conducted sequentially. Initially, petrographic analysis of thin sections and accelerated expansion tests on mortar specimens were performed. These preliminary tests indicated signs of alkali-silica reactivity; however due to inconclusive results, a standardized concrete prism test was subsequently carried out. In addition, ultrasonic pulse velocity and electrical resistivity measurements were monitored as indicators of potential degradation. Petrographic analysis suggested possible reactivity in all three aggregates, although the degree of reactivity could not be determined. Accelerated mortar tests identified only the granitic aggregates as non-reactive. Concrete prisms incorporating quartzite aggregates exhibited no signs of reactivity, regardless of whether the material was used as fine or coarse aggregate. Resistivity measurements proved useful as an experimental control parameter, while ultrasonic pulse velocity monitoring provided insight into potential internal degradation, as it correlated with expansion.